Genetic and clinical characteristics of patients with HNF1A gene variations from the German-Austrian DPV database - Awa, Wendy Lum; Thon, A.; Raile, K.; Grulich-Henn, Jürgen; Meissner, T.; Schober, E.; Holl, R. W. (European journal of endocrinology, 2011)
Objective To determine prevalence, genetic and phenotype characteristics of patients with hepatocyte nuclear factor-1α (HNF1A) variants in the Diabetes Patienten Verlaufsdokumenation (DPV) multicentre database and to examine the influence of HNF1A mutation type, or location on clinical phenotypes. Patients and methods Seventy-one DPV patients were labelled as HNF1A-MODY (MODY3). Forty-four patients carried HNF1A mutations, while 27 patients were found to have HNF1A polymorphisms only. Associations between mutation type/position and age at disease onset, HbAlc, body mass index (BMI), diagnosis, family history and treatment modality were analysed using non-parametric statistics (Wilcoxon test). Results Patients with HNF1A mutations were 36% male, aged 14.1±5.8 years at diagnosis, and slightly overweight (BMI-SDS: +0.8±1.1). Treatment was lifestyle intervention (20.5%), insulin (35.3%), oral anti-diabetic (OAD, 43%) and both insulin+OAD (15.9%). More patients with missense mutations (60%) than patients with nonsense mutations/frameshift (23.8%) did not use insulin (P=0.03). No differences were found with regard to mutation types, isoform or domain. We identified several previously undescribed mutations in the cohort including c.-158insGGGTTGG in the promoter region, G31X, E41X, Q130X, L162P, R245I, A269P, S355X, Q398X, Q473X, Q495X, E508X, P588fs-insGCCA and P588fs-delAC. Patients carrying HNF1A polymorphisms were significantly younger at diagnosis than patients with HNF1A mutations (10.9±4.2 vs 14.19±5.8 years; P=0.027), and all carried I27L, S487N and A98V (n=3). Conclusion HNF1A-MODY is the second most frequent MODY diagnosis registered in the DPV database, and previously undescribed HNF1A mutations account for about one-third of HNF1A-MODY cases. Patients with HNF1A polymorphisms documented as HNF1A-MODY were misclassified. They may have autoantibody-negative type 1B or type 2 diabetes or may have other MODY types.